New Florida Foliage Plant Cultivar: 'Orange Hot' Anthurium - Richard J. Henny; Jianjun Chen; Terri A. Mellich (EDIS)
ENH-1100, a 3-page illustrated fact sheet by R.J. Henny, J. Chen, and T.A. Mellich, describes this new Florida foliage plant cultivar with light salmon orange spathes, available for commercial producers growing finished plants. Includes references. Published by the UF Department of Environmental Horticulture, May 2008.